Pharmacodynamic study of prasugrel or clopidogrel in non-ST-elevation acute coronary syndrome with CYP2C19 genetic variants undergoing percutaneous coronary intervention (PRAISE-GENE trial). (15th April 2020) - Jin, Cai De; Kim, Moo Hyun; Guo, Long Zhe; Jin, Enze; Shin, Eun-Seok; Ann, Soe Hee; Cho, Young-Rak; Park, Jong Sung; Kim, Soo Jin; Lee, Michael S.
Abstract: Background: The CYP2C19*2 or *3 loss-of-function (LOF) allele is associated with high platelet reactivity (HPR) on clopidogrel treatment. East Asians may benefit from a lower dose of prasugrel due to their more potent platelet inhibitory response. The impact of LOF alleles on the pharmacodynamic response to half-dose prasugrel in patients with non-ST-elevation acute coronary syndrome (NSTE-ACS) undergoing percutaneous coronary intervention (PCI) is unknown. Methods: Seventy patients with the LOF alleles were assigned to half-dose prasugrel ( n  = 35, 30-mg load followed by 5 mg daily) or clopidogrel (n = 35, 600-mg load followed by 75 mg daily). The primary endpoint was the rate of HPR, defined as VerifyNow-P2Y12 reaction unit (PRU) >235, at 24 h post loading. Results: Prasugrel achieved a lower PRU compared to clopidogrel after loading (119 [56–175] vs. 245 [189–299]), at 24 h (34 [8–58] vs. 196 [122–244]), and at 30 days (134 [98–189] vs. 203 [144–248]). Prasugrel had a lower rate of HPR after loading (5.7% vs. 57.1%, p <0.001), at 24 h (2.9% vs. 28.6%, p =0.006), and at 30 days (11.4% vs. 34.3%, p =0.004). Prasugrel had a similar rate of optimal platelet reactivity at 30 days (71.4% vs. 60.0%, p =0.450). There was no significant difference in the occurrence of periprocedural myonecrosis within 48 h after PCI with clopidogrel and prasugrel (22.9% vs. 17.1%, p >0.960). Conclusions: Half-dose prasugrel provided potent platelet inhibition in NSTE-ACS patients that were carriers of the CYP2C19*2 or *3 allele, with a lower rate of HPR. Periprocedural myonecrosis was not significantly different in the 2 groups. Highlights: The CYP2C19*2 or *3 allele is associated with high-on-clopidogrel platelet reactivity. Half-dose prasugrel provided potent platelet inhibition in carriers of the CYP2C19*2 or *3 allele. Periprocedural myonecrosis was not significantly different in the 2 groups.